FIR spectra of carbonaceous chondrites pellets irradiated by $He^+$ ions ... - Brunetto, Rosario; Lantz, Cateline (SSHADE/DAYSY (OSUG Data Center), 2023)
Far-IR spectra of carbonaceous chondrite pellets: unirradiated area and area irradiated by $He^+$ ions at 40 keV and a total fluence of $6.10^{16} ions.cm{-2}$. ...